Rapid Growth and Fusion of Protocells in Surface‐Adhered Membrane Networks. Issue 38 (9th August 2020) - Köksal, Elif S.; Liese, Susanne; Xue, Lin; Ryskulov, Ruslan; Viitala, Lauri; Carlson, Andreas; Gözen, Irep
Abstract: Elevated temperatures might have promoted the nucleation, growth, and replication of protocells on the early Earth. Recent reports have shown evidence that moderately high temperatures not only permit protocell assembly at the origin of life, but can have actively supported it. Here, the fast nucleation and growth of vesicular compartments from autonomously formed lipid networks on solid surfaces, induced by a moderate increase in temperature, are shown. Branches of the networks, initially consisting of self‐assembled interconnected nanotubes, rapidly swell into microcompartments which can spontaneously encapsulate RNA fragments. The increase in temperature further causes fusion of adjacent network‐connected compartments, resulting in the redistribution of the RNA. The experimental observations and the mathematical model indicate that the presence of nanotubular interconnections between protocells facilitates the fusion process. Abstract : The emergence and growth of model protocells on networks of lipid nanotubes is accelerated by a moderate increase in temperature. Compartments spontaneously encapsulate RNA fragments from the ambient aqueous solution while growing. With temperature increase, the fusion of adjacent compartments leads to redistribution of the RNA content.